A quartz glass and a preparation method and application thereof
Patent Information
- Application Number
- CN202410264414.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-08
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-03-08
AI Technical Summary
[0004]在现有的化学合成石英玻璃的熔制工艺中,通常将石英玻璃沉积在熔池内,但这样方法制备的石英玻璃的高度受熔池高度限制
[0022]本发明采用化学合成的方法制备石英玻璃,通常将其熔制过程分为初始阶段,扩大阶段,成型阶段和稳定沉积阶段,并且,在成型阶段中,控制石英锭边缘的距离到基底边缘的距离边缘距减小到0.05R~0.15R之间时开始下降基底,并保持沉积面高度不变,使得石英锭的直径便于控制。本发明提出的方法,制得的石英玻璃的高度不受限制,能制得大尺寸的石英玻璃。并且,本方法能实现对合成石英玻璃熔制全过程精确控制,大幅提高沉积工艺稳定性,制备得到等径度、光学均匀性优异的石英玻璃。
Smart Images

Figure CN118206273B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass synthesis technology, and in particular to a quartz glass, its preparation method, and its applications. Background Technology
[0002] Quartz glass refers to glass composed of a single SiO2 component. Its unique structure gives it physical and chemical properties that cannot be replaced by other materials, giving it an irreplaceable position in high-tech fields.
[0003] Applications such as optical exposure systems in lithography machines and photomasks place high demands on the performance of quartz glass, which is often prepared using chemical synthesis methods. There are two main methods for chemically synthesizing quartz glass: Method 1 uses high-purity silicon-containing compounds such as SiCl4 as raw materials, hydrolyzing and melting them in a high-temperature H2-O2 flame, and then synthesizing quartz glass using chemical vapor deposition. This type of quartz glass has a metallic impurity content of less than 1 ppm, but contains approximately 1000 ppm of hydroxyl groups. Method 2 uses plasma chemical vapor deposition, where SiCl4 is oxidized and melted at high temperatures in a hydrogen-free plasma flame. Quartz glass prepared using this process has hydroxyl and metallic impurity contents of less than 1 ppm. In the chemical synthesis of quartz glass, the melting process has a significant impact on the optical properties of the synthesized quartz glass.
[0004] In existing chemical synthesis quartz glass melting processes, quartz glass is typically deposited in a molten pool. However, the height of the quartz glass produced by this method is limited by the height of the molten pool. To synthesize large-size quartz glass, existing technologies deposit and melt silica particles onto the surface of a slab in a vertical deposition furnace to form quartz glass ingots. However, this melting process requires strict control of the furnace temperature and suffers from problems such as untimely feedback and unstable deposition processes. Summary of the Invention
[0005] The main objective of this invention is to provide a quartz glass, its preparation method, and its application. The technical problem to be solved is how to provide a method for synthesizing large-size quartz glass, with timely feedback in the preparation process and stable deposition process, thus making it more suitable for practical use.
[0006] The objective of this invention and the technical problem it solves are achieved by the following technical solution. A method for preparing quartz glass according to this invention includes the following steps:
[0007] (1) Start the flame, heat the substrate, then add the raw materials, react to generate silica particles and deposit them on the aforementioned substrate to generate the initial quartz ingot;
[0008] (2) Based on the relative values of the contact angle θ, diameter R, height h and edge distance of the aforementioned quartz ingot, adjust the flame enthalpy and raw material feed rate to enlarge the aforementioned quartz ingot.
[0009] (3) When the edge distance d decreases to between 0.05R and 0.15R, the aforementioned substrate is lowered, the flame enthalpy value and raw material feed rate are adjusted, and the deposition surface height is kept constant, so that the diameter of the aforementioned quartz ingot is further increased.
[0010] (4) When the diameter of the aforementioned quartz ingot is the same as the diameter of the aforementioned substrate, adjust the flame enthalpy value, and then keep the flame enthalpy value, raw material feed rate, and substrate descent rate stable, so that the aforementioned quartz ingot is deposited stably. The stage of the aforementioned quartz ingot being deposited stably is the stable deposition stage, and quartz glass is obtained.
[0011] The objectives of this invention and the technical problems it addresses can be further achieved by the following technical measures.
[0012] In some embodiments, according to the aforementioned preparation method, in step (1), the raw materials are added when the aforementioned substrate temperature reaches 1750–1850°C.
[0013] In some embodiments, according to the aforementioned preparation method, the enthalpy of the flame in the aforementioned stable deposition stage is 100%, and the enthalpy of the flame in step (1) is 120% to 135%.
[0014] In some embodiments, according to the aforementioned preparation method, in step (2), the aforementioned contact angle θ is 85° to 135°, and the ratio of diameter R to height h, R / h, is 0.8 to 20.
[0015] In some embodiments, according to the aforementioned preparation method, in step (2), if the contact angle θ increases or R / h increases, the flame enthalpy is reduced or the feed rate is increased, but the enthalpy is not less than 80% of the stable deposition stage; if the contact angle θ decreases or R / h decreases, the flame enthalpy is increased or the feed rate is reduced, but the enthalpy is not greater than 135% of the stable deposition stage.
[0016] In some embodiments, according to the aforementioned preparation method, the enthalpy of the flame in the aforementioned stable deposition stage is 100%, and the enthalpy of the flame in step (3) is 110% to 125%.
[0017] In some embodiments, according to the aforementioned preparation method, in step (4), during the stable deposition of the aforementioned quartz ingot, the contact angle θ remains unchanged; if the contact angle θ increases, the flame enthalpy is reduced or the feed rate is increased, but the enthalpy is not less than 95% of the aforementioned stable deposition stage; if the contact angle θ decreases, the flame enthalpy is increased or the feed rate is reduced, but the enthalpy is not greater than 105% of the aforementioned stable deposition stage.
[0018] In some embodiments, according to the aforementioned preparation method, in step (1), a hydrogen-oxygen flame, a methane-oxygen flame, or a plasma flame is used as a heat source.
[0019] The objective of this invention and the solution to its technical problem are also achieved by the following technical solution. A quartz glass according to this invention is prepared using any of the aforementioned preparation methods, and the optical uniformity of the aforementioned quartz glass is less than 2 ppm.
[0020] The objective of this invention and the solution to its technical problems are also achieved by the following technical solutions. This invention proposes the aforementioned application of quartz glass in the field of optics.
[0021] Through the above technical solution, the quartz glass, its preparation method, and its application of the present invention have at least the following advantages:
[0022] This invention employs a chemical synthesis method to prepare quartz glass. The melting process is typically divided into an initial stage, an expansion stage, a shaping stage, and a stable deposition stage. During the shaping stage, the substrate is lowered when the distance between the edge of the quartz ingot and the edge of the substrate is reduced to between 0.05R and 0.15R, while maintaining a constant deposition surface height. This allows for easy control of the quartz ingot diameter. The method proposed in this invention produces quartz glass with no height limitation, enabling the production of large-sized quartz glass. Furthermore, this method achieves precise control over the entire quartz glass melting process, significantly improving the stability of the deposition process and yielding quartz glass with uniform diameter and excellent optical homogeneity.
[0023] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the structure of the apparatus for preparing quartz glass disclosed in the embodiments of the present invention;
[0025] Figure 2 This is a schematic diagram of the initial growth stage of a quartz ingot as disclosed in an embodiment of the present invention;
[0026] Figure 3 This is a schematic diagram of the quartz ingot enlargement stage disclosed in an embodiment of the present invention;
[0027] Figure 4 This is a schematic diagram of the quartz ingot forming stage disclosed in an embodiment of the present invention;
[0028] Figure 5 This is a schematic diagram of the stable deposition stage of quartz ingots disclosed in an embodiment of the present invention.
[0029] Explanation of reference numerals in the attached figures:
[0030] 1. Air intake; 2. Burner; 3. Flame; 4. Deposition furnace; 5. Substrate; 6. Deposition surface; 7. Silica particles; 8. Quartz ingot;
[0031] θ: contact angle; R: quartz ingot diameter; h: quartz ingot height; d: edge distance. Detailed Implementation
[0032] To further illustrate the technical means and effects adopted by the present invention to achieve its intended purpose, the following, in conjunction with the accompanying drawings and preferred embodiments, provides a detailed description of the specific implementation methods, structures, features, and effects of a quartz glass and its preparation method according to the present invention, as well as its application. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable manner.
[0033] These embodiments are provided to make the invention thorough and complete, and to fully express the scope of the invention to those skilled in the art. It should be noted that, unless otherwise specifically stated, the relative arrangement of components and steps, material composition, numerical expressions, and values set forth in these embodiments should be interpreted as merely exemplary and not as limiting.
[0034] This invention proposes a method for preparing quartz glass, comprising the following steps:
[0035] (1) Start flame 3, heat substrate 5, then add raw materials, react to generate silica particles 7 and deposit them on substrate 5 to generate initial quartz ingot 8;
[0036] (2) Adjust the flame enthalpy and raw material feed rate according to the contact angle θ, diameter R, height h and edge distance d of the quartz ingot to enlarge the quartz ingot 8;
[0037] (3) When the edge distance d decreases to between 0.05R and 0.15R, the base 5 is lowered, the height of the deposition surface 6 is kept constant, and the enthalpy of the flame 3 and the feed rate of the raw materials are adjusted to further increase the diameter 8 of the quartz ingot.
[0038] (4) When the diameter of the quartz ingot 8 is the same as the diameter of the substrate 5, adjust the enthalpy of the flame 3, and then keep the flame enthalpy, raw material feed rate and substrate 5 descent rate stable so that the quartz ingot 8 can be deposited stably. The stage of stable deposition of the quartz ingot 8 is the stable deposition stage, and quartz glass is obtained.
[0039] Specifically, such as Figure 1-5As shown, this invention uses chemical vapor deposition to prepare quartz glass. High-purity silicon-containing compounds are used as raw materials. Purified H2 or O2 is used as the carrier gas to carry the vaporized silicon-containing raw material, forming the inlet gas 1, which is fed into the deposition furnace 4 through a feeder. The silicon-containing raw material can be SiCl4, octamethylcyclotetrasiloxane, or silicon tetrafluoride, etc. In the deposition furnace 4, a burner 2 generates a flame 3, causing the silicon-containing raw material to react at high temperature to generate silicon dioxide particles 7, which are deposited on a substrate 5. As the deposition surface 6 grows, the substrate 5 is slowly lowered to maintain the height of the deposition surface 6, gradually forming a quartz ingot 8.
[0040] Step (1) is the initial growth stage of the quartz ingot 8. First, flame 3 is turned on, heating the substrate 5 on one hand and bringing the temperature to the reaction temperature of the silicon-containing raw material on the other. Then, air inlet 1 is turned on, and the silicon-containing raw material in air inlet 1 reacts to generate silicon dioxide particles 7, which are deposited on the substrate 5, and smaller quartz ingots 8 begin to grow, such as... Figure 2 As shown.
[0041] Step (2) is the expansion stage of quartz ingot 8, such as Figure 3 As shown. When the initial quartz ingot 8 grows to a certain size, the flame enthalpy and raw material feed rate are adjusted according to the contact angle θ, diameter R, height h, and edge distance d of the quartz ingot 8. Under high temperature, the high-temperature zone at the top of the quartz ingot increases, the silica melting zone becomes larger, and the diameter of the quartz ingot expands. For example, Figure 3 As shown, the contact angle θ is the contact angle between the quartz ingot 8 and the substrate 5; as Figure 4 As shown, the diameter R is the diameter of the quartz ingot 8, the height h is the height of the quartz ingot 8, and the edge distance d is the distance from the edge of the quartz ingot 8 to the edge of the base 5.
[0042] Step (3) is the forming stage of quartz ingot 8, such as Figure 4 As shown. When the edge distance d of the quartz ingot 8 decreases to between 0.05R and 0.15R, the substrate 5 begins to descend while keeping the height of the deposition surface 6 constant. At the same time, the enthalpy of the flame 3 and the feed rate of the raw materials are adjusted to further expand the diameter R of the quartz ingot 8 so that the diameter R of the quartz ingot 8 is the same as the diameter of the substrate 5.
[0043] When the edge distance d of the quartz ingot 8 is less than 0.05R, the diameter R of the quartz ingot 8 is too large when the substrate 5 is lowered. When the diameter R of the quartz ingot 8 grows to be the same as the diameter of the substrate 5, the quartz melt will flow to the outside of the side wall of the quartz ingot 8, making it difficult to control the diameter R of the quartz ingot 8. When the edge distance d of the quartz ingot 8 is greater than 0.15R, the diameter R of the quartz ingot 8 is too small when the substrate 5 is lowered. It is difficult for the diameter R of the quartz ingot 8 to expand to be the same as the diameter of the substrate 5, resulting in a smaller diameter R of the prepared quartz ingot 8. Therefore, when the edge distance d of the quartz ingot 8 is reduced to between 0.05R and 0.15R, the substrate 5 is lowered.
[0044] The descent of base 5 can be achieved using a mechanical transmission system. For example, a three-phase AC motor drives gears to mesh, which in turn drive a lead screw to move up and down to adjust the height of base 5; or a DC motor drives a belt with a chuck mounted on it, and base 5 is fixed to the chuck. The voltage of the DC motor is adjusted to control the horizontal rotation speed of base 5.
[0045] Step (4) is the stable deposition stage of quartz ingot 8, such as Figure 5 As shown. At this stage, the diameter R of the quartz ingot 8 is the same as the diameter of the substrate 5. By maintaining the flame enthalpy and the raw material feed rate, the quartz ingot 8 is deposited stably, and the height h of the quartz ingot 8 increases steadily. At the same time, the descent rate of the substrate 5 is stable, and the height of the deposition surface 6 remains unchanged.
[0046] The method for preparing quartz glass proposed in this invention can achieve precise control over the entire melting process of synthetic quartz glass, greatly improve the stability of the deposition process, and produce large-sized quartz glass with excellent diameter and optical uniformity.
[0047] In some embodiments, in step (1), the raw materials are added when the base temperature reaches 1750 to 1850°C.
[0048] Specifically, adding the raw materials when the substrate temperature is between 1750 and 1850°C ensures, on the one hand, that the silica particles can be effectively deposited on the substrate and melted into quartz glass more effectively; on the other hand, it ensures the subsequent growth of the quartz ingot 8 is more stable, as excessively high or low temperatures can make it difficult to control the diameter of the quartz ingot 8. Therefore, the raw materials are added when the substrate temperature reaches 1750–1850°C.
[0049] In some embodiments, the enthalpy of the flame in the aforementioned stable deposition stage is 100%, and the enthalpy of the flame in step (1) is 120% to 135%.
[0050] Specifically, when generating the initial quartz ingot 8, the enthalpy of the flame is controlled to be 120%–135% of that in the stable deposition stage. Within this range, it is beneficial to quickly obtain a suitable deposition surface. When the enthalpy of the flame is less than 120% of that in the stable deposition stage, the temperature of the formed quartz melt is lower, its fluidity is poorer, and the diameter of the quartz ingot 8 expands more slowly. When the enthalpy of the flame is greater than 135% of that in the stable deposition stage, the temperature of the formed quartz melt is higher, its fluidity is stronger, and it spreads quickly on the substrate 5, making it more difficult to control the diameter of the quartz ingot 8 and increasing the difficulty of process control. Therefore, the enthalpy of the flame in step (1) is controlled to be 120%–135% of that in the stable deposition stage, with the enthalpy of the flame being 100% of that in the aforementioned stable deposition stage.
[0051] In some embodiments, in step (2), the aforementioned contact angle θ is 85° to 135°, and the ratio of diameter R to height h, R / h, is 0.8 to 20.
[0052] Specifically, controlling the shape of the quartz ingot 8 within this range helps to increase the size of the quartz ingot 8. For example... Figure 3 As shown, the contact angle θ is the contact angle between the quartz ingot 8 and the substrate 5. When the contact angle θ is less than 85°, the height h of the quartz ingot 8 increases relatively quickly while the diameter R increases relatively slowly during expansion. When the contact angle θ is greater than 135°, the height h of the quartz ingot 8 increases relatively slowly while the diameter R increases relatively quickly during expansion. Therefore, the contact angle θ is controlled to be between 85° and 135°. When the ratio of the diameter R to the height h of the quartz ingot 8, R / h, is less than 0.8, the height h of the quartz ingot 8 increases relatively easily while the diameter R increases relatively slowly during expansion. When the ratio of the diameter R to the height h of the quartz ingot 8, R / h, is greater than 20, the height h of the quartz ingot 8 is difficult to increase during expansion. Therefore, the ratio of the diameter R to the height h of the quartz ingot 8, R / h, is controlled to be between 0.8 and 20, so that the vertical cross-section of the quartz ingot 8 is a semi-elliptical shape similar to a steamed bun, allowing both its height h and diameter R to increase relatively quickly.
[0053] In some embodiments, in step (2), if the contact angle θ increases or R / h increases, the flame enthalpy is reduced or the feed rate is increased, but the enthalpy is not less than 80% of the stable deposition stage; if the contact angle θ decreases or R / h decreases, the flame enthalpy is increased or the feed rate is decreased, but the enthalpy is not greater than 135% of the stable deposition stage.
[0054] Specifically, step (2) is the expansion stage of quartz ingot 8. In this stage, if the contact angle θ increases or R / h increases, it indicates that the fluidity of the quartz melt is relatively strong. It can be controlled by reducing the flame enthalpy or increasing the feed rate so that the contact angle θ or R / h is stable within the set range. If the contact angle θ decreases or R / h decreases, it indicates that the fluidity of the quartz melt is relatively poor. It can be controlled by increasing the flame enthalpy or decreasing the feed rate so that the contact angle θ or R / h is stable within the set range.
[0055] In some embodiments, the enthalpy of the flame in the aforementioned stable deposition stage is 100%, and the enthalpy of the flame in step (3) is 110% to 125%.
[0056] Specifically, step (3) is the forming stage of quartz ingot 8. The substrate 5 begins to descend while keeping the deposition surface height unchanged. The enthalpy of the flame is controlled to be 110% to 125% of the enthalpy of the flame in the stable deposition stage. This helps to control the rate of change of the diameter of quartz ingot 8, thereby making the diameter deviation of the final quartz glass smaller and the optical uniformity better.
[0057] In some embodiments, during step (4), when the quartz ingot is deposited stably, the contact angle θ remains unchanged; if the contact angle θ increases, the flame enthalpy is reduced or the feed rate is increased, but the enthalpy is not less than 95% of the aforementioned stable deposition stage; if the contact angle θ decreases, the flame enthalpy is increased or the feed rate is reduced, but the enthalpy is not greater than 105% of the aforementioned stable deposition stage.
[0058] Specifically, step (4) is the stable deposition stage of quartz ingot 8, such as Figure 5 As shown. At this stage, the diameter R of the quartz ingot 8 is the same as the diameter of the substrate 5. By keeping the contact angle θ constant, the quartz ingot 8 can be deposited as stably as possible, with its diameter remaining essentially unchanged. If the contact angle θ increases, it indicates that the fluidity of the quartz melt is relatively strong, which can be controlled by reducing the flame enthalpy or increasing the feed rate. If the contact angle θ decreases, it indicates that the fluidity of the quartz melt is relatively poor, which can be controlled by increasing the flame enthalpy to stabilize the contact angle θ at the set value. At the same time, controlling the flame enthalpy to 95%–105% of that in the stable deposition stage can prevent large changes in the diameter of the quartz ingot 8, which would be difficult to control.
[0059] In some embodiments, according to the aforementioned preparation method, in step (1), a hydrogen-oxygen flame, a methane-oxygen flame, or a plasma flame is used as a heat source.
[0060] Specifically, when using a hydrogen-oxygen flame and selecting SiCl4 as the raw material, the working principle is as follows: High-purity SiCl4 vapor is carried out by purified hydrogen or oxygen and passed into the flame 3 of the hydrogen-oxygen torch. When the hydrogen and oxygen burn, water vapor is generated. The water vapor reacts with the SiCl4 vapor to produce SiO2 and HCl. The silica particles 7 generated by the hydrolysis reaction are sprayed onto the substrate 5. Due to the heating of the flame, the silica adheres to the substrate 5 in a semi-molten state, forming a quartz ingot 8. The chemical reaction formula is:
[0061] 2H₂(g) + O₂(g) = 2H₂O(g)
[0062] SiCl4+2H2O(g)=SiO2+nH20+4HC1(g).
[0063] The present invention proposes a quartz glass prepared by any of the aforementioned preparation methods, wherein the optical uniformity of the aforementioned quartz glass is less than 2 ppm.
[0064] This invention proposes the aforementioned applications of quartz glass in the field of optics. Quartz glass plays a crucial role in optics. It can be used to make high-quality, advanced optical prisms, lenses, windows, absorption cells, and colorimetric cells, and is applied in spectrophotometers, military shooting aiming systems, and more. Examples include quartz glass astronomical reflecting telescopes and laser reflectors. In addition, it includes TiO2-containing quartz glass with an ultra-low coefficient of thermal expansion (zero expansion), radiation-resistant (10 rad) quartz glass, luminescent and filtering quartz glass doped with rare earth or transition metal elements, and Er-doped quartz glass. 3+ Fiber optic amplifiers (EDFAs), fiber optic gyroscopes (FOGs), optical filters, grating fiber laser receivers, planar waveguides, intelligent optical sensors, etc.
[0065] The present invention will be further described below with reference to specific embodiments, but this should not be construed as a limitation on the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention still fall within the scope of protection of the present invention.
[0066] Unless otherwise specified, all materials and reagents mentioned below are commercially available products well known to those skilled in the art; unless otherwise specified, all methods described are methods known in the art. Unless otherwise defined, the technical or scientific terms used should have the ordinary meaning understood by those skilled in the art to which this invention pertains.
[0067] Example 1
[0068] This embodiment employs chemical vapor deposition (CVD) with a hydrogen-oxygen flame heat source, SiCl4 raw material, and a substrate diameter of φ500mm. The flame enthalpy is adjusted by regulating the hydrogen and oxygen flow rates. The specific steps are as follows:
[0069] (1) Initial quartz ingot growth. Start the flame to heat the substrate. Set the hydrogen flow rate to 390 slm and the oxygen flow rate to 185 slm. When the substrate temperature reaches 1780℃, start adding SiCl4 raw material at a feed rate of 11 slm. The silica particles generated by the reaction are deposited on the substrate, and smaller quartz ingots begin to grow.
[0070] (2) Ingot enlargement. The contact angle θ is controlled at 120° and the ratio of the ingot diameter R to the height h is 15.
[0071] (3) Quartz ingot forming. When the edge distance d decreases to 50 mm, the substrate descent is initiated. The hydrogen flow rate is adjusted to 350 slm, the oxygen flow rate to 165 slm, the raw material feed rate to 15 slm, and the substrate descent speed to 5 mm / h.
[0072] (4) Stabilizing deposition. When the diameter of the quartz ingot reaches φ500mm, adjust the hydrogen flow rate to 300slm and the oxygen flow rate to 143slm. Continuously monitor the value of the antenna angle θ and keep it constant at 115°. Maintain the feed rate and descent rate of the raw materials constant to carry out stable deposition of the quartz ingot.
[0073] The quartz glass prepared in this embodiment has a diameter of φ500mm, a diameter deviation of less than 5mm, and an optical uniformity of 1.8ppm.
[0074] Example 2
[0075] This embodiment employs chemical vapor deposition (CVD) with a hydrogen-oxygen flame heat source, SiCl4 raw material, and a substrate diameter of φ300mm. The flame enthalpy is adjusted by regulating the hydrogen and oxygen flow rates. The specific steps are as follows:
[0076] (1) Initial quartz ingot growth. Start the flame to heat the substrate. Set the hydrogen flow rate to 324 slm and the oxygen flow rate to 139 slm. When the substrate temperature reaches 1750℃, start adding SiCl4 raw material at a feed rate of 7 slm. The silica particles generated by the reaction are deposited on the substrate, and smaller quartz ingots begin to grow.
[0077] (2) Ingot enlargement. The contact angle θ is controlled at 135° and the ratio of the ingot diameter R to the height h is 20.
[0078] (3) Quartz ingot forming. When the edge distance d decreases to 15mm, the substrate descent is initiated. The hydrogen flow rate is adjusted to 300slm, the oxygen flow rate to 145slm, the raw material feed rate to 9slm, and the substrate descent speed to 4mm / h.
[0079] (4) Stabilizing deposition. When the diameter of the quartz ingot reaches φ300mm, adjust the hydrogen flow rate to 240slm and the oxygen flow rate to 116slm. Continuously monitor the value of the antenna angle θ and keep it constant at 110°. Maintain the feed rate and descent rate of the raw materials constant to carry out stable deposition of the quartz ingot.
[0080] The quartz glass prepared in this embodiment has a diameter of φ300mm, a diameter deviation of less than 3mm, and an optical uniformity of 1.1ppm.
[0081] Example 3
[0082] This embodiment employs chemical vapor deposition (CVD) with a hydrogen-oxygen flame heat source, SiCl4 raw material, and a substrate diameter of φ1000mm. The flame enthalpy is adjusted by regulating the hydrogen and oxygen flow rates. The specific steps are as follows:
[0083] (1) Initial quartz ingot growth. Start the flame and heat the substrate. Set the hydrogen flow rate to 1080 slm and the oxygen flow rate to 516 slm. When the substrate temperature reaches 1850℃, start adding SiCl4 raw material at a feed rate of 20 slm. The silica particles generated by the reaction are deposited on the substrate, and smaller quartz ingots begin to grow.
[0084] (2) Ingot enlargement. The contact angle θ is controlled at 85° and the ratio of the ingot diameter R to the height h is 0.8.
[0085] (3) Quartz ingot forming. When the edge distance d decreases to 150mm, the substrate descent is initiated. The hydrogen flow rate is adjusted to 990slm, the oxygen flow rate to 473slm, the raw material feed rate to 28slm, and the substrate descent speed to 6mm / h.
[0086] (4) Stabilizing deposition. When the diameter of the quartz ingot reaches φ1000mm, adjust the hydrogen flow rate to 900slm and the oxygen flow rate to 430slm. Continuously monitor the value of the antenna angle θ and keep it constant at 125°. Maintain the feed rate and descent rate of the raw materials constant to carry out stable deposition of the quartz ingot.
[0087] The quartz glass prepared in this embodiment has a diameter of φ1000mm, a diameter deviation of less than 7mm, and an optical uniformity of 1.9ppm.
[0088] Comparative Example 1
[0089] The difference from Example 1 is that in step (3), when the edge distance d decreases to 20 mm, the base descent is initiated.
[0090] After step (4) begins, the diameter of the quartz ingot further increases to φ520mm, and the edges are deformed. The final prepared quartz glass has a diameter between φ490mm and φ520mm, with a diameter deviation of 30mm and an optical uniformity of 5.7ppm.
[0091] Comparative Example 2
[0092] The difference from Example 1 is that in step (3), when the edge distance d decreases to 80 mm, the base descent is initiated.
[0093] Upon reaching the stable deposition stage, although the top diameter of the glass reaches φ500mm, the bottom diameter remains at φ400mm. The final prepared quartz glass has a diameter between φ400mm and φ510mm, with a diameter deviation of 110mm and an optical uniformity of 15ppm.
[0094] The technical features in the claims and / or specification of this invention can be combined, and the combination is not limited to the combinations obtained through reference in the claims. Technical solutions obtained by combining the technical features in the claims and / or specification are also within the scope of protection of this invention.
[0095] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing quartz glass, characterized in that, Includes the following steps: (1) Start the flame, heat the substrate, then add the raw materials, react to generate silica particles and deposit them on the substrate to generate the initial quartz ingot; (2) Adjust the flame enthalpy and raw material feed rate according to the contact angle θ, diameter R, height h and edge distance d of the quartz ingot to enlarge the quartz ingot; the contact angle θ is 85°~135°, the ratio of diameter R to height h R / h is 0.8~20; the edge distance d is the distance from the edge of the quartz ingot to the edge of the substrate; the contact angle θ is the angle between the quartz ingot and the substrate in the direction away from the quartz ingot. (3) When the edge distance d decreases to between 0.05R and 0.15R, the substrate is lowered while keeping the deposition surface height unchanged. At the same time, the flame enthalpy and raw material feed rate are adjusted to further increase the diameter of the quartz ingot. (4) When the diameter of the quartz ingot is the same as the diameter of the substrate, adjust the flame enthalpy value, and then keep the flame enthalpy value, raw material feed rate and substrate descent rate stable to make the quartz ingot deposit stably. The stage of stable deposition of the quartz ingot is the stable deposition stage, and quartz glass is obtained.
2. The preparation method according to claim 1, characterized in that, In step (1), the raw materials are added when the substrate temperature reaches 1750~1850°C.
3. The preparation method according to claim 1, characterized in that, The enthalpy of the flame in the stable deposition stage is 100%, and the enthalpy of the flame in step (1) is 120%~135%.
4. The preparation method according to claim 1, characterized in that, In step (2), if the contact angle θ increases or R / h increases, the flame enthalpy is reduced or the feed rate is increased, but the enthalpy is not less than 80% of the stable deposition stage; if the contact angle θ decreases or R / h decreases, the flame enthalpy is increased or the feed rate is reduced, but the enthalpy is not greater than 135% of the stable deposition stage.
5. The preparation method according to claim 1, characterized in that, The enthalpy of the flame in the stable deposition stage is 100%, and the enthalpy of the flame in step (3) is 110%~125%.
6. The preparation method according to claim 1, characterized in that, In step (4), during the stable deposition of the quartz ingot, the contact angle θ remains unchanged; if the contact angle θ increases, the flame enthalpy is reduced or the feed rate is increased, but the enthalpy is not less than 95% of the stable deposition stage; if the contact angle θ decreases, the flame enthalpy is increased or the feed rate is reduced, but the enthalpy is not greater than 105% of the stable deposition stage.
7. The preparation method according to claim 1, characterized in that, In step (1), a hydrogen-oxygen flame, a methane-oxygen flame, or a plasma flame is used as the heat source.
8. A type of quartz glass, characterized in that, The quartz glass prepared by any one of claims 1-7 has an optical uniformity of less than 2 ppm.
9. The application of the quartz glass according to claim 8 in the field of optics.
Citation Information
Patent Citations
Method for producing large-size and high-uniformity synthetic quartz glass lump
CN113683291A
Process for synthesizing guartz glass by vertical silicon tetrachloride vapor deposition
CN1458097A